If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 2t + -2 = 6t + 9 + -2t Reorder the terms: 5 + -2 + 2t = 6t + 9 + -2t Combine like terms: 5 + -2 = 3 3 + 2t = 6t + 9 + -2t Reorder the terms: 3 + 2t = 9 + 6t + -2t Combine like terms: 6t + -2t = 4t 3 + 2t = 9 + 4t Solving 3 + 2t = 9 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. 3 + 2t + -4t = 9 + 4t + -4t Combine like terms: 2t + -4t = -2t 3 + -2t = 9 + 4t + -4t Combine like terms: 4t + -4t = 0 3 + -2t = 9 + 0 3 + -2t = 9 Add '-3' to each side of the equation. 3 + -3 + -2t = 9 + -3 Combine like terms: 3 + -3 = 0 0 + -2t = 9 + -3 -2t = 9 + -3 Combine like terms: 9 + -3 = 6 -2t = 6 Divide each side by '-2'. t = -3 Simplifying t = -3
| 10.4+3.2f=5f+4 | | 4x-6=4(x+1) | | 3(-9)+2= | | -6x-17=-125 | | -23+22=m-4 | | v-7.92=1.9 | | 31-(3x+5)=3(x+4)+x | | 10x-17=12x+21 | | -0.6x-0.3x+8=-1 | | 12x-5=7x+50 | | x-8.2=4.5 | | 9r-6r+6=6r+6-r | | -2w-4w-24=48 | | 736=4(x+18) | | 2y-15=85-3y | | 6r+4=26r+9 | | 9x+42+15x=4y-13 | | 5(-x)-5= | | 0.6x-1=0.5 | | -296=-8(-8x-3) | | (x+8)(2x+4)(3x-6)=0 | | 50x+50x=300 | | 5x+5-5= | | .05(2t-6)=.10(t+4)-.70 | | -4-3(t-5)= | | 2(x-6)=36 | | 8(z+8)= | | 25=45b | | -7+y=34 | | 4(x+2)+2=7x-3(x-2) | | -93=-1 | | tanx-3cotx=0 |